Use of health services by residents at a seniors-only living facility - Elen Ferraz Teston; Robson Marcelo Rossi; Sonia Silva Marcon (SciELO, 2013)
The objective of the study was to compare the use of medical and dental services by seniors residing at a seniors-only living facility and in the general community. It was a quantitative study, among 50 residents of the living facility and 173 in the general community. The data were collected between November 2011 and February 2012 through a questionnaire, and subjected to statistical analysis. Performance of clinical exams and satisfaction with health services was greater among seniors living in the general community; however, physical therapy treatment was more common among those living in the facility. The use of medical and dental services showed a statistically significant difference. The seniors in both groups need oral health monitoring and those living in the facility also require coverage by the Family Health Strategy. The presence of professionals with the right profile to adequately serve residents and the network of available services are determining factors for the success of this new housing policy.